Breast milk expression among formally employed women in urban and rural Malaysia: A qualitative study - Ismail Tengku Alina; Sulaiman Zaharah; Jalil Rohana; Muda Wan Manan; Man Nik Normanieza (International Breastfeeding Journal, 2012)
Abstract Background Many women are unable to practice exclusive breastfeeding because they are separated from their infants while working. Expressing their breast milk helps them to continue breastfeeding. This study explores the perception and experiences related to the feasibility, acceptability and safety of breast milk expression among formally employed women in Kelantan, Malaysia. Methods A qualitative method using in-depth interviews was conducted from December 2008 to December 2009 among Malay women from urban and rural areas. A snowball sampling method was used to recruit the informants, and the interviews, which were facilitated by an interview guide, were audio-recorded and transcribed verbatim. Thematic analysis was conducted, with construction of codes and themes from each interview. Results Analysis of the interviews with 20 informants identified three themes related to breast milk expression. The themes were as follows: (i) lack of feasibility of expressing breast milk, (ii) negative feelings about expressing breast milk, and (iii) doubts about the safety and hygiene of expressed breast milk. The informants who did not practice exclusive breastfeeding believed that expressing their breast milk was not feasible, commonly because they felt there were not enough facilities for them. They also had negative feelings such as embarrassment. The safety and hygiene of the expressed breast milk was also their main concern. Conclusion More practical and focused education, as well as provision of facilities, is needed for women to effectively and safely express and store their breast milk. The issue of inadequate milk production should be emphasized, especially by encouraging them to express their breast milk as a way to improve milk production.